GE_GERICHTE P/3046/2012 vom 8. Februar 2013 - GE Cour de justice (2013)
SÉQUESTRE(MESURE PROVISIONNELLE); CLASSEMENT DE LA PROCÉDURE; SOUPÇON; CONNEXITÉ; RESTITUTION(EN GÉNÉRAL) | CPP.267; CPP.319; CPP.320